eLocust: an improved desert locust monitoring and early warning system - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
This year´s locust invasion is threatening to devastate crops throughout the Sahel and spark a food crisis in West Africa´s worst locust plague in 15 years. Keith Cressman explains how the FAO?s eLocust sytem - a palmtop computer, GPS device a